ECOLOGICAL CONDITION AND DEVELOPMENT PROBLEMS OF RECREATION ZONES OF FERGANA REGION - Akbarov Golibjon Alisherovich (Research Parks Publishing LLC, 2021)
This article focuses on the ecological status of recreational areas in Fergana region and their changes, as well as the development of special measures to ensure environmental protection, reduce environmental impact, and the development of opportunities and potential of recreational areas in the future.